Systematic Literature Review of the intervention that can inform the design of Access Maths - Paul,Eighteena (Trinity College (Dublin, Ireland). School of Education, 2022)
It is widely acknowledged that opportunities for learning maths are not equal for all students. The general myth that maths is difficult and the tableau of identifying a person as “maths person” or” not a maths person”; makes the learning of mathematics difficult, especially for students from low SES. ”Access Maths” is a potential intervention for students from low SES background to increase their participation and performance in Maths. It also aims at encouraging students to take mathematics in their higher education. The aim of this study is to investigate interventions that can be helpful to improve mathematics performance of students form low SES. The interventions chosen were found to make mathematics teaching and learning more effective. In particular, this work aims at finding design principles for the “Access Maths” Intervention.
Keywords: Leadership and Policy in Education; Education